CORPORATE SOCIAL RESPONSIBILITY (CSR) AS A FORM OF IMPLEMENTING CORPORATE RESPONSIBILITY TO THE ENVIRONMENT AND SOCIAL COMMUNITY - Sanusi Sanusi; Murti Kartini (HERMENEUTIKA : Jurnal Ilmu Hukum, 2022)
Corporate Social Responsibility (CSR) is an improvement in the quality of life which means the ability of humans as individual community members to be able to respond to existing social conditions, be able to enjoy and take advantage of the environment, in other words, it is a way for companies to regulate business processes to produce positive impacts on the environment. community which is an important process as a form of implementation of corporate responsibility to the environment and social community. The government's policy on CSR is contained in Law Number 40 of 2007 concerning Limited Liability Companies. What is safe is that this writing is carried out using a research method with a normative juridical approach, namely legal research that refers to the legal norms contained in the legislation. Corporate responsibility to the public interest can be realized through the implementation of sustainable CSR programs and directly touch aspects of people's lives. The realization of CSR programs is an indirect contribution of the company to the strengthening of overall social capital.